Minitablets as a dosage form convenient for pediatric and geriatric patients - Witold Brniak; Justyna Aleksandra Srebro; Renata Jachowicz (Polish Pharmaceutical Society, 2021)
The individualization of pharmacotherapy including the age and health condition of the patient is a recent trend determining directions of pharmaceutical technology development. Groups of patients that especially need individualization of the therapy include children of different age and elderly with different health condition. Both of them still misses appropriately designed forms of the drugs. One of the dosage forms that enables wide modifications and broad application, convenient for a numerous groups of patients, are minitablets. Minitablets are a solid dosage form of the drug with a diameter from 1 to 3 mm and a mass ranging from several to several dozens of milligrams. They can be administered orally as a conventional and modified release dosage forms, particularly as sustained or enteral release forms. Orodispersible minitablets suitable for children and people with swallowing disorders are also under development. Numerous studies proved that they are convenient even for newborns, infants and toddlers. What is more, they can be much safer alternative for the liquid dosage forms such as syrups or drops. Fast disintegration of such minitablets causes that they can be mixed with soft foods or liquids, including milk and enteral feeding formulas. They can be put directly in the oral cavity or administered with spoon, bottle, or transferred to the stomach or intestines with feeding tubes. Minitablets intended for the oral administration can be applied as an individual dosage units or as a multicompartment dosage form enclosed in a capsule, sachet or administered with a special dispenser. This allows individual dose adjustment within a very wide range. The aim of this study is to present, based on the literature review, the current directions of development of minitablets as a drug form, especially beneficial in pediatric and geriatric patients. This paper also describes methods of minitablets production, compendial requirements regarding quality control of the minitablets, and possibilities of their administration to the patients concerning their age and physiological conditions.